The electrical characterization of ZnO/GaAs heterojunction diode - Soylu, M.; Al-Ghamdi, A. A.; Al-Hartomy, Omar A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2014)
The electrical characteristics of sol-gel synthesized n-ZnO/p-GaAs heterojunction were reported. The values of barrier height and ideality factor for n-ZnO/p-GaAs heterojunction diode were determined to be 0.61 eV and 1.83, respectively. The I-V characteristics of the heterojunction diode exhibit a non-ideal behavior. The ideality factor which is greater than unity was attributed to the series resistance, interface states and interfacial layer. The modified Norde's function combined with conventional forward I-V method was used to obtain the parameters including the series resistance and barrier height (BH). The capacitance-voltage (C-V) measurements were performed in the range of 100 kHz to 1 MHz. The interface distribution profile (D-it) as a function of bias voltage was extracted from the C-V and G(adj)-V characteristics. The interface state density of n-ZnO/p-GaAs diode is of the order of 10(13) eV(-1) cm(-2). Also, the I-V characteristics of n-ZnO/p-GaAs heterojunction diode were investigated in the temperature range of 293-393 K. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Semiconductors; Nanofabrications; Electronic transport